Effect of aromatherapy using classical massage on neuropathic pain among patients with diabetes mellitus - Amira Shawky Mohamed; Fathi Mohammed Soliman; Hend Abdullah Elsheimy; Safaa Mohammed AbdelMotaleb (Cairo : Amira Shawky Mohamed, 2020)
Neuropathic pain is complex symptom to cope with , it has strong impact on patent life. Its treatment needs combining pharmacological and nonpharmacologic therapies. Aim : was to evaluate the effect of aromatheraphy using classical message on the neuropathic pain among patient with type II diabetes mellitus. Hypotheses ; Hb1 (B: the study group who will receive aromatheraphy using classical message will have less neuropathic pain component mean score comparing to patients in the control group who receive only conventional treatment among type II diabetes melltius patients . Setting : medical inpatient wards and the outpatient clinic of diabetes and endocrine disorders at Kasr EL-Aini Hospital Cairo University s
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Surgical Nursing
Issued also as CD
Keywords: Aromatherapy; Classical massage; Diabetes mellitus